Heavy metal pollution in coastal wetlands: A systematic review of studies globally over the past three decades - Li, Chunming; Wang, Hanchen; Liao, Xiaolin; Xiao, Rong; Liu, Kehui; Bai, Junhong; Li, Bo; He, Qiang (Journal of hazardous materials, 2022)
Coastal wetlands are ecosystems lying between land and ocean and are subject to inputs of heavy metals (HMs) from terrestrial, oceanic and atmospheric sources. Although the study on HM pollution in coastal wetlands has been rapidly developing over the past three decades, systematic reviews are still unavailable. Here, by analyzing 3343 articles published between 1990 and 2019, we provided the first holistic systematic review of studies on HM pollution in coastal wetlands globally. The results showed a trend of rapid increases in publications in this field globally, especially over the past ten years. Trends varied greatly among coastal countries, and global trends were primarily driven by the US before 2000, and in China after 2010. We also found that mercury (Hg), cadmium (Cd), and copper (Cu) were the most widely studied HM elements globally, but patterns differed geographically, with Hg being most widely examined in the Americas, Cd in China and India, and lead (Pb) in the western Europe and Australia, respectively. Among different types of coastal wetlands, salt marshes, mangrove forests, and estuaries were the most widely studied, in contrast to seagrass beds and tidal flats. As for ecosystem components, soils/sediments and plants were most extensively investigated, while algae, microbes, and animals were much less examined. Our analysis further revealed rapid emergence of topics on anthropogenic sources, interactions with other anthropogenic environmental changes (climate change in particular), and control and remediation methodology in the literature in the recent ten years. Moving forward, we highlight that future studies are needed to i) better understand the impacts of HM pollution in less studied coastal wetland systems and species, ii) deepen current understanding of the biogeochemical behaviors of HMs under anthropogenic activities, iii) examine interactions with other anthropogenic environmental changes, iv) conceive ecological remediation (i.e., “ecoremediation” as compared to traditional physiochemical remediation and bioremediation) strategies, and v) develop advanced analysis instruments and methods. The perspectives we brought forward can help stimulate many new advances in this field. [Display omitted] •The first holistic systematic review of studies on heavy metal pollution in coastal wetlands globally.•Research increased primarily in the USA before 2000 but China after 2010.•Salt marshes and mangroves are better studied than seagrass beds and tidal flats.•Multi-stressor interactions and remediation are among the fastest developing topics.•Important areas (e.g., ecoremediation) for future research are highlighted.